A Comparative Study of Double Layers Al2O3/Al2O3 and Al2O3/SiO2 Prepared by Microwave and Natural Drying - Ismail, Nur Farhani (International Journal of Integrated Engineering, 2012)
In this work, a comparative study of green multilayered ceramic bodies prepared by natural and microwave drying techniques was investigated. The multilayered ceramic with combination of Al2O3 /Al2O3 and Al2O3/SiO2 samples were prepared via compression method. Alumina powder, Al2O3 with the particle sizes of 90μ, <45μm and silica powder, SiO2 with particle sizes of <45μm were used in this study. Measured linear shrinkage of multilayered ceramic bodies show that microwave drying contribute to lower shrinkage value compared to the natural drying method. The characterization of the microstructure of multilayered ceramic body also shown that microwave technique can create a good bonding structure especially at the critical interface layer. In fact, the implementation of microwave drying also significantly reduced the drying time and produced a good and homogenous final structure